A revised molecular phylogeny reveals polyphyly in Schistura (Teleostei: Cypriniformes: Nemacheilidae) - Sgouros, Katherine; Page, Lawrence M.; Orlofske, Sarah A.; Jadin, Robert C. (Zootaxa, 2019)
There is a general consensus that the genus Schistura (Nemacheilidae), currently with 241 species, is not monophyletic. However, weak morphological synapomorphies and a lack of genetic data for most species of Schistura and their presumptive relatives have prevented meaningful diagnoses of species groups within this genus. To aid in deciphering evolutionary relationships, sequence data from two mitochondrial genes (cytochrome b and D-loop) were implemented in phylogenetic analyses for species of Schistura and other nemacheilids for which data from earlier studies and recently collected material were available. This analysis of 67 nemacheilid species, including 28 species of Schistura, provides the most comprehensive phylogeny of Nemacheilidae to date. In the phylogenetic tree for the combined data set, species of Schistura clustered in three clades. One clade contained 14 species of Schistura and Sectoria heterognathos and was sister to Homatula. A second clade of 11 species of Schistura was in a larger clade with Turcinoemacheilus kosswigi and Nemacheilus corica. The third clade contained three species, all from the Mae Khlong basin of Thailand. Taxonomic implications of these results are discussed; however, a more taxon-rich dataset and nuclear sequence data are needed before making taxonomic changes.